Pine nut shell as a sorbent in fruit winemaking - Ivanova K. R.; Privalova E. A. (Vestnik MGTU)
Reducing the must acidity is a critical task in fruit winemaking due to the need to create favorable conditions for the yeast development and the fermentation of sugars. Acid reduction methods used in traditional winemaking are not suitable for fruit must, since they do not effectively eliminate malic acid which is the main contributor to the fruit wines acidity. The study has examined the possibility of using the adsorption method to reduce the acidity of must obtained from Ussuri pear fruits (titratable acidity of 15.5–18.7 g/dm3) using specially prepared pine nut shells as a sorbent. The must was treated with pine nut shells in a static mode and with stirring; the treatment duration varied from 2 h to 10 days. The pine nut shells have good adsorption capacity for acids contained in pear must and can reduce their amount by 27 %. It has been experimentally established that the pine nut shells have low selectivity for technologically important components of the must and also sorb fermentable sugars and polyphenolic compounds, which may result in an undesirable decrease in the sugar-acid index (SAI) of the must. An increase in the degree of grinding the nut shells helps to increase its adsorption activity. Changing the must processing mode allows you to select conditions under which it is possible to achieve the recommended SAI values.